Shifting Instead of Drifting – Improving Attentional Performance by Means of the Attention Training Technique - Barth, Vincent; Heitland, Ivo; Kruger, Tillmann H. C.; Kahl, Kai G.; Sinke, Christopher; Winter, Lotta (Frontiers in Psychology, 2019)
Background: The Attention Training Technique (ATT) as part of Metacognitive Therapy (MCT) has shown to be a promising treatment element for several psychiatric disorders such as depression and anxiety. ATT predicts improvements of the ability to shift attention away from internal and non-relevant stimuli (e.g. ruminative thoughts) towards the relevant stimuli and aims to increase attentional flexibility and control. The current study investigated the impact of the Attention Training Technique on attentional performance. Methods: 85 healthy participants (29 in two doses ATT, 28 in four doses ATT and 28 in the control group; 18 to 37 years of age) were administered a test battery for attentional performance before and after an intervention of two doses ATT (23 min duration) vs. four doses of ATT (46 min duration) vs. a control condition (non-intervention audio file via headphones. The test battery measured selective attention, inhibition, working memory, and attentional disengagement and comprised the following tasks: dichotic listening, attentional bias, attentional network, stroop, 2-back and a 3-back. Results: After ATT (both two and four doses), reaction time during dichotic listening was significantly faster compared to the control condition. Furthermore, reaction time to neutral stimuli in the attentional bias task was faster after four-doses ATT compared to two doses ATT and the control condition. We found a trend towards a reduced stroop effect for both ATT conditions compared to control group. There were no effects of ATT with regard to the attentional network task, the 2-back or the 3-back task. Conclusions: This first empirical evidence suggests that ATT promotes specific attentional flexibility in healthy participants. Based on the same mechanism, ATT may have beneficial effects on attentional performance in clinical populations and might be a promising tool in both healthy and clinical participants.